Politics in the Representation of Women in Shakespeare’s Twelfth Night - Rai, Ram Prasad (Humanities and Social Sciences Journal, 2023)
The major concern of this paper is to study on how women are represented in the comedy Twelfth Night by William Shakespeare. In the drama, the women characters Viola, Olivia and Maria stand as a challenge to the patriarchy in the society. All of them resist the convention that dominates women. They can work equally well independently as males do in everyday life. In fact, they represent the voice for equality between men and women. The drama reflects the social situation in England during the renaissance when consciousness about women’s rights and capability starts growing. The drama shows that women are also courageous, creative and competent if they are given the opportunity. This study is based on qualitative research methodology. So, I as a researcher have consulted various books and journal articles for support. It applies the concept of feminism seeking equality between men and women. This study will be a help for the coming researchers in the area.